Utilizing the AlphaSign Website to Create Blockchain-Based or Online Digital Signatures - Pauline H. Pattyranie Tan; Agung Rizky; Qurotul Aini; Dwi Nur Ramadhan; Thomas Green (Blockchain Frontier Technology, 2025)
Blockchain is a decentralized system that can track and verify document authenticity, but its open nature poses challenges when dealing with confidential documents or those protected by personal data protection laws. The advancement of digital technology has spurred innovations in signature systems, particularly through the use of the AlphaSign website to create blockchain-based digital signatures.This study aims to enhance the security, transparency, and efficiency of signature issuance using blockchain technology, in alignment with the Sustainable Development Goals (SDGs), particularly SDG 9 (Industry, Innovation, and Infrastructure) and SDG 16 (Peace, Justice, and Strong Institutions).The research method involves the development of a web-based system integrated with blockchain to validate digital signatures. By incorporating automatic validation and signature features, AlphaSign addresses the issues of forgery and the loss of conventional signatures.The findings reveal that implementing blockchain in digital signature systems can improve security by up to 90% and expedite the verification process by up to 70% compared to traditional methods. Additionally, AlphaSign contributes to sustainable digital infrastructure by reducing paper usage and supporting e-administration systems. There fore, this research supports the promotion of safe and efficient digital transformation, aligning with sustainable development principles. The integration of blockchain technology in digital signatures offers a scalable, secure, and efficient solution that advances industry innovation and legal transparency, crucial for the achievement of SDGs.